2019
DOI: 10.3390/ma12172744
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Self-Adaptive Control Method for Plasma Electrolytic Oxidation Processing of Aluminum Alloys

Abstract: Plasma electrolytic oxidation processing is a novel promising surface modification approach for various materials. However, its large-scale application is still restricted, mainly due to the problem of high energy consumption of the plasma electrolytic oxidation processing. In order to solve this problem, a novel intelligent self-adaptive control technology based on real-time active diagnostics and on the precision adjustment of the process parameters was developed. Both the electrical characteristics of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…In PEO, a target metal is subjected to a high voltage which leads to the discharge appearance on the surface with the extremely high temperature and pressure that both provide oxidation of the surface. Usually, PEO treatment is conducted in an aqueous electrolyte made of silicates, phosphates, aluminates, fluorides, and other [7][8][9][10][11][12]. Recently, we have showed a possible implementation of the electrolyte of the molten salt in the PEO process [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In PEO, a target metal is subjected to a high voltage which leads to the discharge appearance on the surface with the extremely high temperature and pressure that both provide oxidation of the surface. Usually, PEO treatment is conducted in an aqueous electrolyte made of silicates, phosphates, aluminates, fluorides, and other [7][8][9][10][11][12]. Recently, we have showed a possible implementation of the electrolyte of the molten salt in the PEO process [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[11,14,15] The experimental conditions employed in the PEO treatment allow the control of the morphology and microstructure of the oxide film, influencing other properties. [15][16][17] Additionally, the PEO condition can be obtained by different electrical stimulation, such as galvanostatic or potentiostatic (DC PEO), [18][19][20] alternate current, [21,22] pulsed potential/ current, [23,24] and hybrid [25,26] modes. The galvanostatic DC mode is handy for monitoring the stages of the oxide growth and mapping the system to comprehend its electrochemical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach to the tailored coatings, a few closed loop methods have been reported. Yang et al , suggested pulse shape monitoring to avoid current spike and associated detrimental discharge appearance. Hermanns et al applied in situ image analysis of microdischarges acting on the sample surface to prevent large destructive discharges generation by automatic narrowing of the pulse width.…”
Section: Introductionmentioning
confidence: 99%